Distinctive features of stump volume change in a fresh lower limb amputee with Parkes-Weber syndrome. (21st October 2014) - Yahata, Tetsutaro; Takeuchi, Akihiko; Yoshida, Shinya; Tsuchiya, Hiroyuki
Abstract : A 23-year-old man with Parkes-Weber syndrome suffered ischaemia on the toes of his left foot with overactive high-shunting. The symptoms were refractory and persistent, and trans-tibial amputation was finally performed; all detectable active lesions that had been involved by arteriovenous shunts were removed. Marked stump swelling was found a couple of times postoperatively when compression treatment was absent. Despite excessive enlargement, conventional compression treatment using elastic bandages was effective in suppressing the enlargement rapidly and in controlling the stump volume. Additionally, 8 months postoperatively, stump enlargement has not recurred using silicone liner as compressive measures. We speculated that marked stump swelling may have been caused by postoperative temporal venous congestion due to the residual varicosities in the stump. Excessive volume change of the stump confused us and stagnated prosthetic rehabilitation. Recognition of such clinical characteristics will facilitate smooth and favourable prosthetic rehabilitation in fresh amputees with Parkes-Weber syndrome.